Synthesis and antiproliferative activities of OSW-1 analogues bearing 2-acylamino-xylose residues. Issue 14 (23rd May 2019) - Sun, Lijun; Wang, Ruina; Wang, Xiaobo; Dang, Yongjun; Li, Wei; Yu, Biao
Abstract : We synthesized 38 OSW-1 analogues with 2-acylamino xylose residues and found that the antitumor activities could be greatly enhanced. Abstract : OSW-1 and SBF-1 are well studied saponins with exceptionally potent antitumor activities. Herein, we report the syntheses of a library of 38 C22-ester analogues bearing 2-acylamino xylose residues. SAR studies show that the introduction of the 2-acylamino xylose residues could further increase the antitumor activities as many as 40 folds than those of SBF-1 and the (1→3)-disaccharide linkage is crucial to the activities. A highly potent probe (3 ) bearing photoactivatable and clickable residues has been identified.